Gastrointestinal Parasitic Infection of Swamp Buffalo in Banten Province, Indonesia: Prevalence, Risk Factor, and Its Impact on Production Performance - N. Nurhidayah; F. Satrija; E. B. Retnani (Faculty of Animal Science, Bogor Agricultural University, 2019)
Gastrointestinal parasitic infections cause economic losses in large ruminant’s production including swamp buffalo in tropical areas. The basic epidemiological data and impact of the infections in swamp buffaloes in Indonesia are very limited. A cross sectional study was conducted to measure the prevalence, to identify the risk factor, and to evaluate the impact of gastrointestinal parasites infection on production performance (BCS and girth) of swamp buffalo in five Sentra Peternakan Rakyat (SPR) in Banten Province, Indonesia. A total of 340 fecal samples were collected and examined microscopically using modified McMaster technique. The risk factors scrutinized in this study were sex, age, farming managements, and agroclimate. Infection was found in 128 buffaloes (37.65%) consisted of Nematodes, i.e. Toxocara (0.88%), Strongyles (8.24%), Trichuris (5.29%), Strongyloides (2.94%), and Coccidia of Eimeria (30%). Age of buffaloes was the only significant risk factor for the infection. The highest infection rate was occurred in the group of pre-weaned calves (63.83%) and the lowest was found in the adults (29.66%). Pre-weaned calve group was 8.519 and 8.435 times more likely to be infected with nematodes and protozoa, respectively. The Spearman correlation test showed that the girth was negatively low-correlated and significantly to the EPG of Toxocara vitulorum, the number of protozoa oocyst as well as the prevalence of gastrointestinal parasitic infections. BCS was not related to the infections. In conclusion, low prevalence of gastrointestinal parasitic infections potentially reduce the production performance of swamp buffaloes in the SPRs of Banten Province, Indonesia.